Vestibular Aqueduct and Temporal Bone Radioanatomy in Patients With and Without Meniere Disease: A Retrospective Cross-Sectional Analysis With Implications for Endolymphatic Sac Surgery - Jeanne Bernard; Dario Ebode; Priya Vishnumurthy; Antonino Maniaci; Maria-Pia Tuset; Mario Lentini; Ralph Haddad; Giannicola Iannella; Mary Daval; Justin Michel; Stéphane Gargula (Clinical and Experimental Otorhinolaryngology)
Objectives. The vestibular aqueduct (VA) exhibits significant anatomical variability. These variations and their spatial relationships with neighboring structures may pose technical challenges during endolymphatic sac surgery. We aimed to characterize the anatomical features of the VA and its relationship with surrounding structures in patients with severe Meniere disease compared to controls using high-resolution computed tomography (CT). Methods. This retrospective study included 65 patients (126 ears) who underwent temporal bone CT. The Meniere group comprised 26 patients (26 affected ears) meeting the American Academy of Otolaryngology-Head and Neck Surgery (AAO-HNS) criteria for intractable disease; the contralateral ear group included 24 ears, and the control group comprised 39 patients (76 ears) with unrelated conditions. Measurements included VA thickness (A), width (B/B´), the distance between the posterior semicircular canal (PSCC) and posterior fossa (C), PSCC depth (D/D´), and operculum depth (E/E´). Correlations were analyzed, and k-means clustering was applied to classify anatomical variations. Reliability was assessed using intra- and inter-observer tests. Results. VA width (B) correlated positively with the PSCC–meningeal distance (C) (r=0.683, P<0.001) and negatively with PSCC depth (D´) (r=–0.290, P<0.01) and operculum depth (E´) (r=–0.520, P<0.001). Patients with a narrower VA exhibited a reduced PSCC–meningeal distance and a deeper operculum position. The Meniere group demonstrated significantly narrower VA and shorter PSCC–dura distances compared to controls (P<0.001). Cluster analysis identified three anatomical patterns, with 61.5% of intractable Meniere ears versus 14.5% of controls and 41.6% of contralateral ears falling into the cluster characterized by smaller VA dimensions, shorter PSCC–dura distances, and deeper operculum positions. Conclusion. A narrow VA correlates with a reduced PSCC–meningeal distance and a deeper operculum position, potentially complicating endolymphatic sac surgery. These anatomical variations are more prevalent in patients with severe Meniere disease, highlighting the need for tailored surgical approaches.